Reading Sedgwick - Berlant, Lauren Gail, 1957-2021 (Theory Q., 2019)
The contributors to Reading Sedgwick reflect on the long and influential career of Eve Kosofsky Sedgwick, whose pioneering work in queer theory has transformed understandings of affect, intimacy, politics, and identity.